Prevalence, severity and risk factors for asthma in school-going adolescents in KwaZulu Natal, South Africa - Maia Lesosky; Refiloe Masekela; Reratilwe Mphahlele (BMJ Open Respiratory Research, 2023)
Background Asthma remains highly prevalent, with more severe symptoms in low-income to middle-income countries (LMICs) compared with high-income countries. Identifying risk factors for severe asthma symptoms can assist with improving outcomes. We aimed to determine the prevalence, severity and risk factors for asthma in adolescents in an LMIC.Methods A cross-sectional survey using the Global Asthma Network written and video questionnaires was conducted in adolescents aged 13 and 14 from randomly selected schools in Durban, South Africa, between May 2019 and June 2021.Results A total of 3957 adolescents (51.9% female) were included. The prevalence of lifetime, current and severe asthma was 24.6%, 13.7% and 9.1%, respectively. Of those with current and severe asthma symptoms; 38.9% (n=211/543) and 40.7% (n=147/361) had doctor-diagnosed asthma; of these, 72.0% (n=152/211) and 70.7% (n=104/147), respectively, reported using inhaled medication in the last 12 months. Short-acting beta agonists (80.4%) were more commonly used than inhaled corticosteroids (13.7%). Severe asthma was associated with: fee-paying school quintile (adjusted OR (CI)): 1.78 (1.27 to 2.48), overweight (1.60 (1.15 to 2.22)), exposure to traffic pollution (1.42 (1.11 to 1.82)), tobacco smoking (2.06 (1.15 to 3.68)), rhinoconjunctivitis (3.62 (2.80 to 4.67)) and eczema (2.24 (1.59 to 3.14)), all p<0.01.Conclusion Asthma prevalence in this population (13.7%) is higher than the global average (10.4%). Although common, severe asthma symptoms are underdiagnosed and associated with atopy, environmental and lifestyle factors. Equitable access to affordable essential controller inhaled medicines addressing the disproportionate burden of asthma is needed in this setting.